Enhancing Educational Quality through Principals' Human Resources Management Strategies - M. Shoffa Saifillah Al Faruq; Ahmad Sunoko; M. Asep Fathur Rozi; Agus Salim (STAI Hubbulwathan Duri, 2024)
This article investigates the principal's strategies for enhancing the quality of education through human resource management at MTs Al Anwar Sarang. The school faces several challenges, including teacher discipline, the mismatch between academic qualifications and teaching assignments, and the mastery of learning methods and media. A qualitative research method was employed, involving in-depth interviews to gather data on the strategies used by the school principal to improve education quality. Interviewees included principals, educators, education personnel, and other relevant parties. The data were analyzed using data condensation techniques as described by Miles and Huberman, followed by presentation and conclusion drawing. The study revealed that the principal implemented several effective strategies. These included granting educators the freedom to develop professionally, providing motivation and support, delegating training responsibilities, and involving resource persons. Additional support was given through adequate facilities, sufficient time, family meetings, and rewards. These strategies led to improvements in individual skills and fostered a dynamic, collaborative, and reward-focused school environment. Specifically, they enhanced educator discipline, improved the quality of teaching, and bolstered mastery of learning methods and media. The findings suggest that the principal’s policies, which promote autonomy and professional development, significantly contribute to educational improvements. Furthermore, the strategies created a positive atmosphere and a solid community of educators, supporting sustainable growth for the entire educational team. This study provides valuable insights for educators, policymakers, and researchers into how strategic human resource management can enhance education quality. The pragmatic framework introduced here demonstrates how school principals can effectively guide human resource management to achieve significant educational improvements.